THE EFFECT OF PLIOMETRIC DEPTH JUMP TRAINING ON THE JUMP HEIGHT OF VOLLEYBALL EXTRACURRICULAR PARTICIPANTS AT SMAN 5 MALANG IN THE 2024/2025 SCHOOL YEAR - Danang Dwi Prasetyo (Indonesian Conditioning Coaches, 2025)
Jumping ability is one of the main components in a volleyball game, especially during smash, block, and serve. Optimal jump height provides a competitive advantage, both in attack and defense. This study aims to determine the effect of pliometric depth jump training on the jump height of volleyball extracurricular participants at SMAN 5 Malang in the 2024/2025 school year. Pliometric depth jump training was chosen because it was proven to have an effect in increasing leg muscle strength, and explosive power. This study used an experimental method with a one group pre-test-post-test design. The population in this study were 10th grade students who were members of volleyball extracurricular activities at SMAN 5 Malang, with a total sample of 25 students. The training program was carried out for six weeks with a frequency of three times per week on Monday, Wednesday, Friday. The vertical jump test was used to measure jump height before and after the training program. The data obtained were analyzed using paired sample t-test with the help of SPSS software. The results showed an increase in jump height after the subject received treatment in the form of pliometric depth jump training. The average increase in jump height was 3-5 cm. The statistical test resulted in a significance value of <0.001, which indicates the effect of pliometric depth jump training on the vertical jump ability of volleyball extracurricular participants of SMAN 5 Malang. In addition, the results of this study indicate that pliometric depth jump training can also improve athletes' body coordination, balance, and reaction time, which are important elements in volleyball. Based on the results of the study, it can be concluded that the depth jump pliometric training program is effective for increasing the jump height of volleyball extracurricular participants of SMAN 5 Malang.